Quantitative Ultrasound of Orofacial Muscles in Infants from 6 Months to 5 Years: Collecting Normal Values - L.J. Lagarde, M.; van den Engel-Hoek, L. (Current Medical Imaging, 2017)
Introduction: The purpose of this study was to obtain normal values for muscle thickness (MT) and echogenicity of orofacial muscles in infants between 6 months and 5 years old. The data may be compared with data of patients with a neuromuscular disorder (NMD) to differentiate between healthy infants and patients and to explain oromotor dysfunction. Aims of this study were to provide normal values for the thickness of the tongue, digastric muscles, temporalis muscles and masseter muscles and the echogenicity of the digastric muscles, masseter muscles, temporalis muscles and geniohyoid muscles, and to establish the influence of gender, age, height and bodyweight on the thickness and echogenicity of the orofacial muscles. Methods: Ultrasound measurements of orofacial muscles were performed in 56 healthy infants. Echogenicity was determined using a gray-scale analysis. MT was measured by placing electronic calipers at predetermined locations. Results: MT of the digastric muscles, the temporalis muscles and the tongue depended on bodyweight. Echogenicity of the temporalis muscles depended on bodyweight and age, echogenicity of the digastric muscles depended on age and echogenicity of the masseter muscles depended on bodyweight. Gender only influenced the echogenicity of the geniohyoid muscle. Equations for calculating z-scores for echogenicity and MT were determined. Conclusion: This study provides normal values for MT and echogenicity of orofacial muscles in infants between 6 months and 5 years old. Difficulty in chewing and swallowing may be explained by comparing the data found in this study with the data of patients.
Keywords: orofacial muscles